2004
DOI: 10.1186/1476-0711-3-11
|View full text |Cite
|
Sign up to set email alerts
|

Physician behaviour for antimicrobial prescribing for paediatric upper respiratory tract infections: a survey in general practice in Trinidad, West Indies

Abstract: BackgroundUpper respiratory tract infections (URTIs) are among the most frequent reasons for physician office visits in paediatrics. Despite their predominant viral aetiology, URTIs continue to be treated with antimicrobials. We explored general practitioners' (GPs) prescribing behaviour for antimicrobials in children (≤ 16 years) with URTIs in Trinidad, using the guidelines from the Centers for Disease Control and Prevention (CDC) as a reference.MethodsA cross-sectional study was conducted on 92 consenting GP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 23 publications
0
8
1
Order By: Relevance
“…From their results, they suggest that (1) diagnostic uncertainty is the factor that most influences doctors' prescribing, and, (2) contrary to previously published literature, parental pressure is not associated with antibiotic prescribing. We would like to raise some questions and report our experience.…”
Section: To the Editorcontrasting
confidence: 75%
See 2 more Smart Citations
“…From their results, they suggest that (1) diagnostic uncertainty is the factor that most influences doctors' prescribing, and, (2) contrary to previously published literature, parental pressure is not associated with antibiotic prescribing. We would like to raise some questions and report our experience.…”
Section: To the Editorcontrasting
confidence: 75%
“…However, physicians in previous survey studies have acknowledged and admitted to bowing to parental pressure. 1,2,5 It is possible that physicians may admit to being influenced by parental pressure in general but do not always link this to their decision to prescribe in an individual situation. Thus the potential explanations for our failure to detect parental pressure as an important influence on antibiotic prescribing are likely manifold.…”
Section: Replymentioning
confidence: 96%
See 1 more Smart Citation
“…A limitation however is whether prescribers would take advantage of available diagnostic services or tools. Studies have shown that this does not always happen ( Mohan et al . 2004 ; Polage et al .…”
Section: Discussionmentioning
confidence: 99%
“…Mohan et al in 2004 reported that the five most frequent URTIs presenting in children in Trinidad are the common cold, pharyngitis, tonsillitis, sinusitis and acute otitis media in rank order 3. Further only 12% of physicians would request laboratory tests before prescribing antimicrobials; 87.5% of physicians considered them unnecessary; 30% felt that a clinical diagnosis was sufficient; and 51.3% said the long waiting periods for results rendered laboratory impractical 3…”
Section: Introductionmentioning
confidence: 99%